2012
DOI: 10.1155/2012/639427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kalsis, A Dietary Supplement, on Bone Metabolism in the Ovariectomized Rats

Abstract: We studied the ability of Kalsis, a food supplement that contains selenium, citric acid, and vitamin E, to prevent the effects of ovariectomy on bone loss. Six-month-old, Wistar female rats were studied. Groups (n = 12): SHAM: sham-operated rats; OVX: ovariectomized rats, treated with vehicle; OVX + Kalsis: ovariectomized rats treated with Kalsis (25 mg/kg/day) for 3 months. Bone mineral density (BMD) was determined by DXA in lumbar spine and femur. Computerized microtomography (μCT) in femur and serum osteoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…In addition, the µCT evaluation revealed more trabecular bone with the anodised implants, particularly the NT-Sr3h sample, than with Ti. Consistent with a previous study 38 , ovariectomy produced a significant increase in bone remodelling, in terms of both resorption (CTX-I) and formation (PINP). The current study also demonstrates that NT-Sr decreases the CTX-I levels induced by OVX.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the µCT evaluation revealed more trabecular bone with the anodised implants, particularly the NT-Sr3h sample, than with Ti. Consistent with a previous study 38 , ovariectomy produced a significant increase in bone remodelling, in terms of both resorption (CTX-I) and formation (PINP). The current study also demonstrates that NT-Sr decreases the CTX-I levels induced by OVX.…”
Section: Discussionsupporting
confidence: 91%
“…The number of slices was 20, and the total volume analyzed was 4.84 mm 3 . The procedures were performed following a method that was previously described (Montero et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3C. Mean fibrosis scores at baseline and after 3 months of treatment in both the groups Viusid ® is a powerful antioxidant because of the Antioxidant activity of glycyrrhizic acid is over 100 times stronger than that of Vitamin E and the antioxidant capacity of Viusid ® is further increased by "Molecular Activation", which is about 800% more potent than its previous non-activated state [9,10,11,12]. Evidences showed that Viusid ® inhibits oxidative stress, lipid per-oxidation (MDA) and several pro-inflammatory cytokines (TNF-alpha, IL-1 &IL-6) involved in fibrogenesis process.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity of glycyrrhizic acid, the most important active ingredient of the supplement, was found to be over 100 times stronger than that of Vitamin E [10]. Furthermore, the manufacturer used a patented bio-technology namely "Molecular Activation" to activate and increase the overall antioxidant activity of Viusid ® (before activation the antioxidant capacity was 1.1 points and after activation the antioxidant capacity significantly increased to 9.9 points) which is about 800% more potent than its previous non-activated state ( Figure 1) [9,11,12]. Evidences showed that Viusid ® inhibits oxidative stress, lipid per-oxidation (MDA) and several pro-inflammatory cytokines (TNF-alpha, IL-1 &IL-6) involved in fibrogenesis process.…”
Section: Introductionmentioning
confidence: 99%